Smart Solid Waste Collection System Based on Internet of Things - Pynam, Venkateswarlu; Rajeti, Roje Spandana; Bobbadi, Manasa (International Journal of Computer Sciences and Engineering, 2018)
Solid waste makes an ever growing problem at local and as well as universal levels. The disposal of solid waste is polluting all the factors of environment at regional and global levels. The world is facing a great challenge due to increasing urbanization as there is rise in the amount of generated waste and littering due to high demand for food products and other essentials. The main problem is faced in the developing countries than in developed countries was the continuous flow of garbage in all places where public people move around to create the unhygienic conditions. It may invoke several contagious diseases among the nearby people. To avoid such situations and to improve the cleaning, ‘smart waste management system using on IOT’ is proposed. The waste in the dustbins is checked with the help of sensors used in the system, the smallest version, E- nose on a chip containing both the sensors and the processing components then information is sent to the required control room through GSM/GPRS system. RL78/G11 Microcontroller is used to communicate the sensor system with GSM system. An android application is been modeled to monitor the information related to the waste for different selected locations.